Proteome profiling of exosomes derived from human primary and metastatic colorectal cancer cells reveal differential expression of key metastatic factors and signal transduction components. Issue 10 (3rd June 2013) - Ji, Hong; Greening, David W.; Barnes, Thomas W.; Lim, Justin W.; Tauro, Bow J.; Rai, Alin; Xu, Rong; Adda, Christopher; Mathivanan, Suresh; Zhao, Wei; Xue, Yanhong; Xu, Tao; et al.
Abstract : Exosomes are small extracellular 40–100 nm diameter membrane vesicles of late endosomal origin that can mediate intercellular transfer of RNAs and proteins to assist premetastatic niche formation. Using primary (SW480) and metastatic (SW620) human isogenic colorectal cancer cell lines we compared exosome protein profiles to yield valuable insights into metastatic factors and signaling molecules fundamental to tumor progression. Exosomes purified using OptiPrep™ density gradient fractionation were 40–100 nm in diameter, were of a buoyant density ∼1.09 g/mL, and displayed stereotypic exosomal markers TSG101, Alix, and CD63. A major finding was the selective enrichment of metastatic factors (MET, S100A8, S100A9, TNC), signal transduction molecules (EFNB2, JAG1, SRC, TNIK), and lipid raft and lipid raft‐associated components (CAV1, FLOT1, FLOT2, PROM1) in exosomes derived from metastatic SW620 cells. Additionally, using cryo‐electron microscopy, ultrastructural components in exosomes were identified. A key finding of this study was the detection and colocalization of protein complexes EPCAM‐CLDN7 and TNIK‐RAP2A in colorectal cancer cell exosomes. The selective enrichment of metastatic factors and signaling pathway components in metastatic colon cancer cell‐derived exosomes contributes to our understanding of the cross‐talk between tumor and stromal cells in the tumor microenvironment.